Associations of cardiovascular and all-cause mortality events with oxygen uptake at ventilatory threshold. (1st June 2017) - Kunutsor, Setor K.; Kurl, Sudhir; Khan, Hassan; Zaccardi, Francesco; Laukkanen, Jari A.
Abstract: Background: Oxygen uptake (VO2 ) at ventilatory threshold (VT), is a cardiopulmonary exercise testing parameter which may be a proxy for peak VO2 . We aimed to assess the associations of VO2 at VT with sudden cardiac death (SCD), fatal coronary heart disease (CHD) and cardiovascular disease (CVD), and all-cause mortality. Methods and results: VO2 at VT was assessed during a submaximal exercise test using respiratory gas analyzers in the Kuopio Ischemic Heart Disease cohort of 1639 middle-aged men. Hazard ratios (HRs) (95% CIs) were assessed. During a median follow-up of 25.6 years, 121 SCDs, 202 fatal CHDs, 312 fatal CVDs, and 703 all-cause mortality events occurred. VO2 at VT was correlated with peak VO2 ( r = 0.90) and linearly associated with each outcome. Comparing extreme quartiles of VO2 at VT, the HRs (95% CIs) for SCD, fatal CHD, fatal CVD, and all-cause mortality on adjustment for established risk factors were 0.37 (0.18–0.78), 0.32 (0.18–0.57), 0.45 (0.30–0.69), and 0.50 (0.38–0.64) respectively. The HRs were 1.02 (0.36–2.91), 1.43 (0.63–3.25), 1.46 (0.79–2.71), and 1.02 (0.69–1.51) respectively on further adjustment for peak VO2 . Addition of VO2 at VT to a CVD mortality risk prediction model containing established risk factors significantly improved risk discrimination and reclassification at 25 years. Conclusions: There are linear and inverse associations of VO2 at VT with fatal cardiovascular and all-cause mortality events, which are dependent on peak VO2 . Inclusion of VO2 at VT in the standard established risk factors panel significantly improves the prediction and classification of long-term CVD mortality risk. Highlights: Oxygen uptake (VO2 ) at ventilatory threshold (VT) is correlated with peak VO2 . VO2 at VT is associated with fatal cardiovascular disease and all-cause mortality. The associations are inverse and consistent with graded relationships. The associations are however partly dependent on peak VO2 . VO2 at VT improves prediction of the long-term risk for cardiovascular mortality.